2016
DOI: 10.1038/srep36305
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of the World Trade Center dust-activated mdig and c-myc signaling circuit linked to multiple myeloma

Abstract: Several epidemiological studies suggested an increased incidence rate of multiple myeloma (MM) among first responders and other individuals who exposed to World Trade Center (WTC) dust. In this report, we provided evidence showing that WTC dust is potent in inducing mdig protein and/or mRNA in bronchial epithelial cells, B cells and MM cell lines. An increased mdig expression in MM bone marrow was observed, which is associated with the disease progression and prognosis of the MM patients. Through integrative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…There are now several reports describing MINA overexpression in multiple cancer types including colorectal [ 54 ], lung [ 30 , 55 ], esophageal [ 56 ], lymphoma [ 57 ], cholangiocarcinoma [ 58 ], gingival squamous cell carcinoma [ 59 ], neuroblastoma [ 60 ], liver [ 61 , 62 ], gastric [ 63 ], pancreatic [ 64 ], multiple myeloma [ 65 ], and breast cancers [ 66 ]. Importantly, MINA expression was associated with poor prognosis in some, but not all, of these studies [ 56 , 60 , 63 , 65 67 ]. Interestingly, MINA overexpression positively correlated with immunohistochemical markers of proliferation in several studies [ 58 60 , 62 , 67 ].…”
Section: Minamentioning
confidence: 99%
“…There are now several reports describing MINA overexpression in multiple cancer types including colorectal [ 54 ], lung [ 30 , 55 ], esophageal [ 56 ], lymphoma [ 57 ], cholangiocarcinoma [ 58 ], gingival squamous cell carcinoma [ 59 ], neuroblastoma [ 60 ], liver [ 61 , 62 ], gastric [ 63 ], pancreatic [ 64 ], multiple myeloma [ 65 ], and breast cancers [ 66 ]. Importantly, MINA expression was associated with poor prognosis in some, but not all, of these studies [ 56 , 60 , 63 , 65 67 ]. Interestingly, MINA overexpression positively correlated with immunohistochemical markers of proliferation in several studies [ 58 60 , 62 , 67 ].…”
Section: Minamentioning
confidence: 99%
“…Consequentially, cancer research accounts for a large portion (21%) of the funds awarded. There are descriptive and analytic studies examining cancer mortality and incidence, with a few studies examining mechanisms or treatment [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. There are also notable reviews [ 77 , 78 ].…”
Section: Research Portfoliomentioning
confidence: 99%
“…Another study indicated WTC-dusts are highly capable of inducing mdig (mineral dust-induced gene, also known as mina53, MINA, or NO52) in normal B cells and malignant myeloma cell lines. The levels of mdig mRNA and protein are associated with multiple myeloma progression and prognosis [ 74 ]. Still, the current evidence of increased multiple myeloma in WTC populations is inconsistent.…”
Section: Research Portfoliomentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence also suggests that JMJD10 has lysine-(K) demethylase (KDM) activity in various experimental conditions. In particular, studies have reported the involvement of JMJD10/MINA53 in histone methylation by antagonizing trimethyl lysine 9 on histone H3 (H3K9me3) [7][8][9][10][11][12][13][14][15]. Later studies indicated that JMJD10/MINA53 was also involved in the repression of H3K36me3 [16], H3K27me3, and H4K20me3 [17].…”
Section: Introductionmentioning
confidence: 99%